Changes in Urination According to the Sound of Running Water Using a Mobile Phone Application - Kwon, Whi-An; Kim, Sung Han; Kim, Sohee; Joung, Jae Young; Chung, Jinsoo; Lee, Kang Hyun; Lee, Sang-Jin; Seo, Ho Kyung (PLOS ONE, 2015)
Objective The sound of running water (SRW) has been effectively used for toilet training during toddlerhood. However, the effect of SRW on voiding functions in adult males with lower urinary tract symptoms (LUTS) has not been evaluated. To determine the effect of SRW on urination in male patients with LUTS, multiple voiding parameters of uroflowmetry with postvoid residual urine (PVR) were assessed according to the presence of SRW played by a mobile application. Methods Eighteen consecutive male patients with LUTS were prospectively enrolled between March and April 2014. Uroflowmetry with PVR measured by a bladder scan was randomly performed once weekly for two consecutive weeks with and without SRW in a completely sealed room after pre-checked bladder volume was scanned to be more than 150 cc. SRW was played with river water sounds amongst relaxed melodies from a smartphone mobile application. Results The mean age of enrolled patients and their mean International Prostate Symptom Score (IPSS) were 58.9 ± 7.7 years (range: 46–70) and 13.1 ± 5.9, respectively. All patients had not been prescribed any medications, including alpha-blockers or anti-muscarinic agents, in the last 3 months. There was a significant increase in mean peak flow rate (PFR) with SRW in comparison to without SRW (15.7 mL/s vs. 12.3 mL/s, respectively, p = 0.0125). However, there were no differences in other uroflowmetric parameters, including PVR. Conclusions The study showed that SRW from a mobile phone application may be helpful in facilitating voiding functions by increasing PFR in male LUTS patients.